Aerosol and Air Quality Research - SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer.)
Aerosol and Air Quality Research (AAQR) is an international journal that covers all aspects of aerosol science and technology, atmospheric science and air quality related issues. It encompasses a multi-disciplinary field, including: Aerosol, air quality, atmospheric chemistry and global change Air toxics (hazardous air pollutants (HAPs), persistent organic pollutants (POPs)) - Sources, control, transport and fate, human exposure Nanoparticle and nanotechnology Sources, combustion, thermal decomposition, emission, properties, behavior, formation, transport, deposition, measurement and analysis Effects on the environments Air quality and human health Bioaerosols Indoor air quality Energy and air pollution Pollution control technologies Invention and improvement of sampling instruments and technologies Optical/radiative properties and remote sensing Carbon dioxide emission, capture, storage and utilization; novel methods for the reduction of carbon dioxide emission Other topics related to aerosol and air quality.
Keywords: Earth sciences; Geography; Environment; Environmental health; Earth and Environmental Sciences; Environmental Sciences; Environmental Health